Echocardiographic estimation of pulmonary vascular resistance in advanced lung disease. (6th January 2023) - DesJardin, Jacqueline T.; Svetlichnaya, Yana; Kolaitis, Nicholas A.; Hays, Steven R.; Kukreja, Jasleen; Schiller, Nelson B.; Zier, Lucas S.; Singer, Jonathan P.; De Marco, Teresa
Abstract: Noninvasive assessment of pulmonary hemodynamics is often performed by echocardiographic estimation of the pulmonary artery systolic pressure (ePASP), despite limitations in the advanced lung disease population. Other noninvasive hemodynamic variables, such as echocardiographic pulmonary vascular resistance (ePVR), have not been studied in this population. We performed a retrospective analysis of 147 advanced lung disease patients who received both echocardiography and right heart catheterization for lung transplant evaluation. The ePVR was estimated by four previously described equations. Noninvasive and invasive hemodynamic parameters were compared in terms of correlation, agreement, and accuracy. The ePVR models strongly correlated with invasively determined PVR and had good accuracy with biases of <1 Wood units (WU), although with moderate precision and wide 95% limits of agreement varying from 5.9 to 7.8 Wood units. The ePVR models were accurate to within 1.9 WU in over 75% of patients. In comparison to the ePASP, ePVR models performed similarly in terms of correlation, accuracy, and precision when estimating invasive hemodynamics. In screening for pulmonary hypertension, ePVR models had equivalent testing characteristics to the ePASP. Mid‐systolic notching of the right ventricular outflow tract Doppler signal identified a subgroup of 11 patients (7%) with significantly elevated PVR and mean pulmonary artery pressures without relying on the acquisition of a tricuspid regurgitation signal. Analysis of ePVR and determination of the notching pattern of the right ventricular outflow tract Doppler flow velocity envelope provide reliable insights into hemodynamics in advanced lung disease patients, although limitations in precision exist.